PENGARUH PERSEPSI DUKUNGAN ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN AFEKTIF DAN KESEJAHTERAAN PSIKOLOGIS SEBAGAI VARIABEL INTERVENING (Studi Pada Karyawan Bagian Produksi Permata Farish Group) - Yeni Novita Sari; Ismi Darmastuti (Diponegoro Journal of Management, 2022)
This study aims to determine and analyze the effect of perceived organizational support on employee performance through affective commitment and psychological wellbeing as a mediation at a convection company in Indonesia, precisely located in Bandung, namely Permata Farish Group. This study uses primary data sources derived from the distribution of questionnaires and short interviews with several research respondents and secondary data through journals, books, websites and relevant data obtained from companies. The sampling technique used in this study is total sampling. The data analysis technique is Partial Least Square (PLS) analysis using the SmartPLS 3.2.9 application program to determine the path coefficient and specific indirect effects of exogenous variables on endogenous variables. The results of statistical testing using a p-value of 0.05 indicate that the perception of organizational support has a positive and significant effect on affective commitment, psychological well-being and employee performance. Affective commitment and psychological well-being also have a positive and significant effect on employee performance. Another finding is that affective commitment and psychological well-being can mediate the effect of perceived organizational support on employee performance with psychological well-being values greater than affective commitment.